Estudo de propriedades no estado fresco de argamassas de revestimento com escória de aciaria BSSF - Amancio, Felipe Alves (2019)
The generation of waste has become a preponderant issue for the steel industry due to the large amount of waste generated, which requires greater planning in the destination of these by-products. Allied to this, the shortage of good quality inputs near the consumer centers has increased the interest for products that cause less environmental impact and lower costs. However, the use of alternative materials in civil construction should be thoroughly examined in order to ensure satisfactory performance as well as adequate durability of the final product. In this sense, the objective of this work is to evaluate the influence of the Baosteel Slag Short Flow (BSSF) steel slag as a small aggregate in the fresh state properties of coating mortars. The experimental work involved physical-chemical characterization of the slag produced at Companhia Siderúrgica do Pecém, as well as characterization of the properties of mortars produced in the plastic state (consistency index, w/c ratio, Squeeze-flow, specific mass, built-in air and water retention). Three traces of simple mortars (cement) and three traces of mixed mortars (cement and lime) were substituted for natural sand by BSSF steel slag. Three replicates were performed for each assay and the results were analyzed statistically by analysis of variance (ANOVA). It can be verified that mortars with higher slag contents required a greater amount of water to obtain the spread on the table of consistency, which was fixed at 260 ± 5mm. The substitution of part of the natural sand for the slag causes a significant increase in the specific mass in the fresh state, while in the incorporated air content, although there is a small reduction, there is no significant influence in this property. As for water retention, while in cement mortars, the substitution content of sand for slag significantly influences the reduction of water retention in mixed mortars. This fact was not observed. In relation to the rheological behavior of squeeze-flow, it was found that although the mortars with BSSF steel slag presented higher ratio a / c, they obtained lower values of displacements for a maximum load of 1kN. From the results, it can be concluded that the 20% substitution content presents similar properties of water retention in simple mortars. As for the rheological behavior of mortars by squeeze-flow, it was found that the substitution of sand by steel slag influences negatively.